Autophagy up-regulation upon FeHV-1 infection on permissive cells - Ferrara, Gianmarco; Sgadari, Mariafrancesca; Longobardi, Consiglia; Iovane, Giuseppe; Pagnini, Ugo; Montagnaro, Serena (Frontiers in Veterinary Science, 2023)
FeHV-1 is a member of the Herpesviridae family that is distributed worldwide and causes feline viral rhinotracheitis (FVR). Since its relationship with the autophagic process has not yet been elucidated, the aim of this work was to evaluate the autophagy mediated by FeHV-1 and to determine its proviral or antiviral role. Our data showed that autophagy is induced by FeHV-1 in a viral dose and time-dependent manner. Phenotypic changes in LC3/p62 axis (increase of LC3-II and degradation of p62) were detected from 12 hours post infection using western blot and immuno-fluorescence assays. In a second step, by using late autophagy inhibitors and inducers, the possible proviral role of autophagy during FeHV-1 infection was investigating by assessing the effects of each chemical in terms of viral yield, cytotoxic effects, and expression of viral glycoproteins. Our findings suggest that late-stage autophagy inhibitors (bafilomycin and chloroquine) have a negative impact on viral replication. Interestingly, we observed an accumulation of gB when cells were pretreated with bafilomycin, whereas the opposite effect was observed when an autophagy inducer was used. The importance of autophagy during FeHV-1 infection was further supported by the results obtained with ATG5 siRNA. In summary, this study demonstrates FeHV-1-mediated autophagy induction, its proviral role, and the negative impact of late autophagy inhibitors on viral replication.